World‐Wide FINGERS Network: A global approach to risk reduction and prevention of dementia. Issue 7 (5th July 2020) - Kivipelto, Miia; Mangialasche, Francesca; Snyder, Heather M.; Allegri, Ricardo; Andrieu, Sandrine; Arai, Hidenori; Baker, Laura; Belleville, Sylvie; Brodaty, Henry; Brucki, Sonia M.; Calandri, Ismael; Caramelli, Paulo; et al.
Abstract: Reducing the risk of dementia can halt the worldwide increase of affected people. The multifactorial and heterogeneous nature of late‐onset dementia, including Alzheimer's disease (AD), indicates a potential impact of multidomain lifestyle interventions on risk reduction. The positive results of the landmark multidomain Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER) support such an approach. The World‐Wide FINGERS (WW‐FINGERS), launched in 2017 and including over 25 countries, is the first global network of multidomain lifestyle intervention trials for dementia risk reduction and prevention. WW‐FINGERS aims to adapt, test, and optimize the FINGER model to reduce risk across the spectrum of cognitive decline—from at‐risk asymptomatic states to early symptomatic stages—in different geographical, cultural, and economic settings. WW‐FINGERS aims to harmonize and adapt multidomain interventions across various countries and settings, to facilitate data sharing and analysis across studies, and to promote international joint initiatives to identify globally implementable and effective preventive strategies.